The State and Society in Conflict Resolution in Indonesia (Conflict Area of West Kalimantan and Central Kalimantan) - Heru Cahyono (Deputy of Social Sciences and Humanities, the Indonesia Institute of Sciences (LIPI), 2008)
Several bloody communal conflicts shook some areas in Indonesia from the late 1990s to early 2000s, including widespread violent conflicts in West and Central Kalimantan. Two groups, the Dayaks and the Malays, both asserting their status as indigenous ethnic groups, fought another ethnic group, migrants from Madura (the Madurese). The disturbances began in late February 2001 in Central Kalimantan. Thousands of Dayaks attacked the Madurese. There was violence and killing in almost all villages. The disturbances began in Sampit City and spread to Kuala Kapuas, Pangkalan Bun and Palangka Raya. More than 400 Madurese died and 80 000 people were forced to leave Kalimantan.